Fear of COVID-19 in pregnant women during their pre-immunization and post-immunization against SAR-CoV-2, at the Carquín health post, 2021 - Valladares-Bazalar, Paolo Neil (2021)
Introduction: Studies show a high prevalence of psychological disorders during pregnancy. According to the analysis and systemic review of 40 studies in 17 countries conducted by The Lancet Global Health during 2020-2021, there is an increase in maternal depression, termination of ectopic pregnancies and maternal-fetal deaths. As a consequence of not going to the Health Service Provider Institutions, for fear of contagion of COVID-19. Objective: To compare the level of fear of COVID-19 in pregnant women during their pre-immunization and post-immunization against SARS-CoV-2, at the Carquín Health Post, 2021. Materials and Methods: Non-experimental, descriptive - comparative design; observational, prospective, longitudinal descriptive and descriptive level. Population of 60 pregnant women treated at the Carquín Health Post in 2021 and a sample of 54 pregnant women. Inclusion criteria: pregnant women without a diagnosis of COVID-19. Exclusion criteria: pregnant women diagnosed with COVID-19. The survey technique was used using the "Scale of Fear of COVID-19 Peruvian version" tool. During the intervention, an orientation was given regarding informed consent and their rights to information privacy. The data collected were entered and processed in SPSS Statistics v.26. Subsequently, they were analyzed using the frequency tables and the Chi Square test, giving a level of significance greater than 0.08. Results: During the pre-immunization period, 62.96% (n = 3) presented high fear, 5.56% (n = 17) had low fear and 31.5% (n = 34) had regular fear. While in the post-immunization period, 11.1% (n = 6) presented high fear, 9.3% (n = 5) regular fear and 79.6% (n = 43) low fear. Conclusions: There is a significant decrease in the level of fear of COVID-19 in pregnant women, during post-immunization to SARS-CoV-2 compared to the pre-immunization period.